2022
DOI: 10.5937/intrev2204131b
|View full text |Cite
|
Sign up to set email alerts
|

The role of travel influencers in sustainable tourism development

Abstract: Tourism, as one of the main industries at the global level, can provide many benefits, primarily economic, however the growing trend of tourist travel has begun to cause incalculable damage to the environment, cultural heritage and to affect the lifestyle of the local population of tourist destinations. In recent years, sustainable development in tourism has emerged as a necessity, but in order for such processes to be adequately completed, it is necessary to reprogram people's awareness of environmental prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Travel influencers are recognized as opinion leaders in the tourism context (Kotler et al, 2009). Previous literature investigated the role of travel influencers from diverse aspects, such as their role in shaping tourists' travel decisions (Pop et al, 2021), promoting tourism destinations (Xu (Rinka) & Pratt, 2018), engaging in word-of-mouth (George et al, 2021), enhancing sustainable tourism development (Baltezarević et al, 2022;Kapoor et al, 2022), and destination image (Gholamhosseinzadeh et al, 2023). Furthermore, previous studies evaluated the quantitative impacts of travel influencers such as follower numbers, clicks, likes, and reposts.…”
Section: Opinion Leadership Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Travel influencers are recognized as opinion leaders in the tourism context (Kotler et al, 2009). Previous literature investigated the role of travel influencers from diverse aspects, such as their role in shaping tourists' travel decisions (Pop et al, 2021), promoting tourism destinations (Xu (Rinka) & Pratt, 2018), engaging in word-of-mouth (George et al, 2021), enhancing sustainable tourism development (Baltezarević et al, 2022;Kapoor et al, 2022), and destination image (Gholamhosseinzadeh et al, 2023). Furthermore, previous studies evaluated the quantitative impacts of travel influencers such as follower numbers, clicks, likes, and reposts.…”
Section: Opinion Leadership Theorymentioning
confidence: 99%
“…Travel influencers are recognized as opinion leaders within the tourism factors and are ranked among the external factors that influence tourists' behaviors (Kotler et al, 2009). Previous literature has investigated the role of travel influencers in shaping tourists' travel decisions (Pop et al, 2021), promoting tourism destinations (Xu (Rinka) & Pratt, 2018), engaging in word-of-mouth (George et al, 2021), enhancing sustainable tourism development (Baltezarević et al, 2022;Kapoor et al, 2022), and destination image (Gholamhosseinzadeh et al, 2023). However, there is limited focus on the cultural and geographical characteristics of travel influencers in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in outcomes among studies examining the impact of influencers on sustainable consumption can be attributed to differences in their scope, extent, and sampling. It is worth noting that most existing research has focused on the impact of influencers on specific products, such as food [18][19][20][21], clothing [14,22], freight [16], and tourism [23], and has targeted specific demographics, such as children [24] and millennials [14,25]. Although these studies have yielded valuable insights, the literature to date has not provided a comprehensive answer to the question of whether influencers have a broad impact on sustainable consumption and, if so, how consumers' perceptions of influencers' characteristics affect various types of sustainable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The above fact is best confirmed by the data of the World Tourism Organization on the number of people who traveled abroad, that is, who participated in international tourist movements: in 1950, about 25 million, in 1970, 166 million, in 1990, 435 million, in 2010 over 935 million, and in 2019 close to one billion and 500 million [21; 22]. When the number of domestic tourists is added to this number, which is many times higher, it can be concluded that tourism, in modern conditions of development, represents the "leading world industry" and that its influence on the process of economic development is becoming more and more intense [3].…”
Section: Introductionmentioning
confidence: 99%